Pancasila in the Digital Era: Strengthening the Character and Political Participation of Village Communities - Huda, Mirojul; Ilhamuddin, Muhammad Farid; Wahyuni, Jauhar; Lina, Hasna Nur; Gusti G P, Esa Putra Bayu (CV. Rayyan Dwi Bharata, 2025)
Indonesia needs to re-actualize the values of Pancasila, which have proven to be an effective solution in dealing with various national problems, including the issue of intolerance. As the foundation of the state, Pancasila plays an essential role in shaping the attitudes and behavior of society. However, these values are increasingly being eroded, as seen from the weakening of Pancasila's knowledge and practice in everyday life, which triggers disputes and divisions. Pancasila has gone through various political dynamics, from parliamentary democracy to the reform era, and remains relevant as an ideology that unites Indonesia's diversity. With a foundation in ethnic, religious, and cultural diversity, Pancasila reflects harmonious national wealth and is a shared cultural heritage.